A new species of Toxorhinus Lacordaire (Coleoptera: Curculionidae: Dryophthorinae; Rhynchophorini) from Ecuador - Anderson, Robert S. (Zootaxa, 2023)
Toxorhinus amarillo Anderson, new species (Coleoptera: Curculionidae: Dryophthorinae; Rhynchophorini), is here described from Ecuador (Cotopaxi, Biochoa Otonga). The species is compared to the other two species in the genus.